Natural Reading in Parkinson’s Disease With and Without Mild Cognitive Impairment - Stock, Lena; Krüger-Zechlin, Charlotte; Deeb, Zain; Timmermann, Lars; Waldthaler, Josefine (Frontiers in Aging Neuroscience, 2020)
Background: Patients with Parkinson’s disease (PD) show eye movement abnormalities and frequently complain about difficulties in reading. So far, it is unclear whether basal ganglia dysfunction or cognitive impairment has a greater impact on eye movements during reading. Objective: To analyze eye movement behavior during a natural reading task with respect to cognitive state and dopaminergic therapy in PD and healthy controls. Methods: Eye movements of 59 PD patients and 29 age- and education-matched healthy controls were recorded during mute, self-paced reading of a text. 25 cognitively normal PD patients performed the task additionally in off medication state. Clinical assessment included a comprehensive neuropsychological test battery and the motor section of MDS-UPDRS. Results: PD-MCI was diagnosed in 21 patients. Reading speed was significantly reduced in PD-MCI compared to healthy controls and PD patients without MCI due to higher numbers of progressive saccades. Cognitively intact PD patients showed no significant alterations of reading speed or eye movement pattern during reading. The fixation duration tended to be prolonged in PD compared to healthy controls and decreased significantly after levodopa intake. Scores for executive functions, attention and language correlated with reading speed in the PD group. Conclusions: The present study is the first to reveal 1) reduced reading speed with altered reading pattern in PD with MCI and 2) a relevant impact of levodopa on fixation duration during reading in PD. Further research is needed to determine whether therapeutic interventions, e.g. levodopa or neuropsychological training, improve the subjective reading experience for patients with PD.